MIDWIFERY MANAGEMENT OF NORMAL LABOR IN MRS. W, G1P0A0, WITH A 39-WEEK GESTATION AT NIAR PRATAMA CLINIC, TIMBANG DELI, MEDAN AMPLAS DISTRICT, MEDAN CITY, NORTH SUMATRA 2025 - Arini, Nazua; Manalu, Irmawati; Damanik, Lisa Putri Utami; Sinaga, Siti Nurmawan; Juniarsih (Mitra Husada Health Internasional Conference (MIHHICo), 2026)
Background: Normal labor is a physiological process that occurs at the end of pregnancy, involving the delivery of the fetus, placenta, and fetal membranes through the birth canal. Although labor is a natural event, primigravida mothers often require more intensive observation and support because they have no prior childbirth experience. Appropriate and comprehensive midwifery care during labor is essential to ensure maternal and fetal well-being, support the normal progress of labor, prevent complications, and provide a safe and positive childbirth experience.Objective: This case study aims to describe the implementation of comprehensive midwifery care in a woman with normal labor and to evaluate the outcomes of the interventions provided during the first stage of labor. Method: This study used a case study method with a midwifery care management approach. The subject of this case study was Mrs. W, a 20-year-old woman, G1P0A0, with a gestational age of 39 weeks, who came to Klinik Pratama Niar Timbang Deli on April 28, 2026, with complaints of lower abdominal tightening that had been occurring for several hours and was becoming more frequent. Data were collected through history taking, observation, physical examination, obstetric examination, and documentation using the SOAP method. Results: The assessment results showed that Mrs. W was in the latent phase of the first stage of labor with good general condition, vital signs within normal limits, and a fetal heart rate of 150 beats per minute. Obstetric examination revealed a single live intrauterine fetus in cephalic presentation, with the fetal head having entered the pelvic inlet. The midwifery care provided included informing the mother about the examination results, teaching relaxation and breathing techniques during contractions, encouraging rest between contractions, ensuring adequate nutritional and fluid intake, providing communication, information, and education about the signs of labor, and giving emotional support to the mother and her family. Conclusion: Comprehensive midwifery care is effective in supporting normal labor, especially in primigravida mothers, by improving maternal comfort, maintaining maternal and fetal stability, and promoting safe labor progress.